Pemeriksaan Kesehatan Internasional Dengan Screening Test Penyakit Tidak Menular pada Masyarakat di Distric Aileu, Timor Leste - Miftahur Ainul Fikriyah; Muhammad Fakhrur Afif; Novemika Fitria Aswinda; Hendra Dwi Cahyono; Andi Eka Pranata (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Community service through health checks in villages that are far from access to health on the international stage is an initiative to overcome this inequality. Therefore, the University of Dr. Soebandi actively plays a role in developing health internationally by carrying out community service through non-communicable disease screening activities in neighboring countries, namely Timor Leste, specifically in the Seloi Malere suco, Aileu district. Through this approach, it is hoped that early detection of health problems can be carried out, increase awareness about health in the community, build international cooperation, and contribute to more equitable global health development. The stages carried out before carrying out this community service activity were confirmation with the Seloi Malere tribal chief, after that the tribal chief met with the xefe aldeia (RW head) from Kabas Fatin, Cotabauru and Maurusa for coordination with the residents, the day of implementation, and the location where the activity is carried out. In the examination data, it was also found that many people in Aileu District have high blood pressure.